2020
DOI: 10.1063/5.0022929
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous isotropic turbulence in four spatial dimensions

Abstract: Direct Numerical Simulation is performed of the forced Navier-Stokes equation in four spatial dimensions. Well equilibrated, long time runs at sufficient resolution were obtained to reliably measure spectral quantities, the velocity derivative skewness and the dimensionless dissipation rate. Comparisons to corresponding two and three dimensional results are made. Energy fluctuations are measured and show a clear reduction moving from three to four dimensions. The dynamics appear to show simplifications in four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
2

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(40 citation statements)
references
References 99 publications
6
32
2
Order By: Relevance
“…In the DNS study of Berera et al (2020), the observed scaling of the energy spectrum was consistent with that predicted by K41 in both the three-and four-dimensional cases insofar 10 -8 10 -10 as within a given dimension the energy spectra were found to collapse upon scaling by Kolmogorov variables. However, the spatial dimension was found to have an influence on the shape of the energy spectrum in the near dissipative region.…”
Section: Energy and Transfer Spectrasupporting
confidence: 77%
See 4 more Smart Citations
“…In the DNS study of Berera et al (2020), the observed scaling of the energy spectrum was consistent with that predicted by K41 in both the three-and four-dimensional cases insofar 10 -8 10 -10 as within a given dimension the energy spectra were found to collapse upon scaling by Kolmogorov variables. However, the spatial dimension was found to have an influence on the shape of the energy spectrum in the near dissipative region.…”
Section: Energy and Transfer Spectrasupporting
confidence: 77%
“…A higher value was found in the EDQNM of Bos et al (2007), however, they take a different choice of λ 1 which will directly influence the value found. In four dimensions we find C 4d ε,∞ = 0.96 lower than the value of 1.26 found in DNS (Berera et al 2020). Since C ε is defined in terms of large-scale quantities, where the forcing is active, these discrepancies between DNS and EDQNM are not surprising given the differences at small k seen in figure 3.…”
Section: Dissipative Anomalycontrasting
confidence: 55%
See 3 more Smart Citations